Upaya Peningkatan Mutu Pendidikan Melalui Profesionalisme Guru Madrasah - Rumina (TABYIN: JURNAL PENDIDIKAN ISLAM, 2020)
Teachers are the spearhead of children's morality. Besides, he provides examples of moral behavior as well as formulates basic moral values ​​for students, and that part of the result is that teachers unconsciously educate them morally and in the end it will lead to the birth of quality human development based on good morals, for that teachers are required to be professional teachers in carrying out their professional authority, so that in the end it will improve the quality of education. Research procedures: in this study using qualitative methods, where these methods have natural characteristics, namely the natural setting. The main sources of research data are all MA Bahrul Ulum Nganjuk teachers and the sources of oral data were obtained through interviews. While the data collection techniques in this study were to use observation, documentation and interview techniques. When all the data has been collected, the data is clarified and analyzed using descriptive analytic techniques. And the validity of the data can be done by checking the data by means of in-depth observation and triangulation so that it can produce valid data. The results of the study (from filling out questionnaires and interviews) briefly show that the teachers at MA Bahrul Ulum Nganjuk have fulfilled the aspects of being a professional teacher, which is seen from the level of education so that they have the authority to carry out the teaching and learning process. The professional qualifications of MA Bahrul Ulum Nganjuk's teachers are quite good in terms of the diplomas they have, the experience and activity of the teachers are very good, and are supported by teachers who are 85% already certified. And the teacher's effort to improve the quality of education is through the experience of working groups of teachers, the availability of adequate facilities and infrastructure, following upgrading / MGMP with various teachers from dinganjuk existing schools.